Developing a system dynamic model for product life cycle management of generic pharmaceutical products: Its relation with open innovation - Atefeh Mousavi; Mehdi Mohammadzadeh; Hossein Zare (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The purpose of this study is to identify elements that influence the sale of generic pharmaceutical products during their life cycle in order to achieve more comprehensive planning and to prevent a decline stage of the product life cycle (PLC). We used a system dynamic model to identify the behaviors of demand, supply, and competition as three major subsystems of PLC in generic pharmaceutical products. We first investigated the PLC patterns of 527 medicines to identify their “reference mode”, determined the causal loop of the pharmaceuticals phase of PLC based on both an in-depth literature review and experts' opinions, and finally simulated a quantitative dynamic model based on real-world data between 2012 and 2019 from Iran. Based on the results, “total demand and accurate forecasting”, “marketing efforts”, and “R and D activities of a firm” are the most critical factors involved in the formation of a generic drug PLC. An increase of 20–50% of manufacturers' marketing and R and D activities can raise sales by more than 50% in the decline stage of the PLC. The product life cycle can give generic manufacturers more insights into the processes leading to declining sales of their products. PLC may help to prevent a product from entering the decline stage even if the total demand for a generic drug is dropping in the market.
Keywords: 650; open innovation dynamics; pharmaceutical industry; product life cycle; system dynamic